온도센서를 이용한 전력설비의 온라인 상태 감시 - 최용성; 김선재; 김영민; 송환기; 이경섭; Choi, Yong-Sung; Kim, Sun- Jae; Kim, Yeong-Min; Song, Hwao-Kee; Lee, Kyung-Sup (전기학회 논문지 P권, 57(2), 2008)
Condition monitoring technologies allow achieving this goal by minimizing downtime through the integrated planning and scheduling of repairs indicated by condition monitoring techniques. Thermal runaways induced by conduction problems deteriorate insulating material and cause disruptive dielectric discharges resulting in arcing faults. Therefore, having the ability to directly measure the temperature of the contacts while in service will provide more information to determine the true condition of the equipment. It allows connective measures to be taken to prevent upcoming failure. Continuous temperature monitoring and event recording provides information on the energized equipment's response to normal and emergency conditions. On-line temperature monitoring helps to coordinate equipment specifications and ratings, determine the real limits of the monitored equipment and optimize facility operations. Using wireless technique eliminates any need for special cables and wires with lower installation costs if compared to other types of online condition monitoring equipment. In addition, wireless temperature monitoring works well under difficult conditions in strategically important locations. Wireless technology for on -line condition monitoring of energized equipment is applicable both as stand alone system and with an interface for power quality monitoring system. The paper presents the results of wireless temperature monitoring: of electrical equipment at a power plant.